Mekanisme Pengawasan Pemilu Di Indonesia - Musfialdy Musfialdy (Sosial Budaya, 2012)
Election is the embodiment of popular sovereignty which is the absolute will of the Indonesian people after setting himself as a democratic country. Therefore as part of democratic nations, Indonesia has recognized the sovereignty of the people who affirmed in the Constitution of 1945. To create a healthy degree of competition, participatory, and has a degree higher representation, and have a clear accountability mechanism, then the general election should be implemented in higher quality over time. Implementation of the efforts made in improving quality is to establish and carry out oversight functions election.